Proposals for the 2nd Five Year Plan Health Department (Public Health) Vol. II Government of Madhya Bharat - Planning Commission (Planning Commission, 1955)
The object of the Scheme is to promote Health consciousness among the people by organising Health Propaganda throughout the state. Health Propaganda is a specialised task and therefore requires centrailsed direction supply of literature to the public with a view to educate them on public Health matters. It is considered essential to educate public to fight against ignorance and prevention and cure of sickness as as the promotion of positive health.
Government of Madhya Bharat